HUBUNGAN KOMUNIKASI TERAPEUTIK DENGAN TINGKAT KECEMASAN PASIEN BARU di RUANG UGD PUSKESMAS TAMANAN BONDOWOSO - Novita, Rini (Jurnal Keperawatan Profesional, 2020)
One of the emotional problems disorders that are often encountered and has a psychological impact seriously is anxiety. Anxiety is an unclear and diffuse concern related to feelings of uncertainty and helplessness. Anxiety is an emotional experience that is short-lived and reasonable response, when individuals faceup pressure or events that threaten their lives, both internal and internal threats. Anxiety that happened and hav a relation ship with medical condition often found when patient came to healt hfacility, whichone of themisemergencyroom. Therapeutic communication methods provide understanding between nurses and patients with the aim of helping patients clarify and reduce the burden of the mind and are expected to eliminate anxiety. This study aims to knowabout relationship between therapeutic communication and the anxiety level of new patients.This study useddescription korelation with cross sectional approach. Sample are171 people. Instrument used for data collection is the questionnaire, anddata analysis used the Spearman Rho test. Therapeutic communication of nurses was mostly in good categorywas128 respondents (74.9%). The anxiety level of new patients is not anxious categorywere 127 respondents (74.3%). Rho Spearman's test results obtained a coefficient (r) of 0.901 with a p value of 0,000. Because p<0.005 then H0 is rejected.Conclusion,There is a significan trelation ship between therapeutic communication and the anxiety level of new patients in the emergency room at Tamanan Bondowoso Public Health Center.